THE INFLUENCE OF COCONUT MILK ON THE INTESTINAL STRUCTURE OF BALB/C MICE IMMUNIZED WITH COW'S MILK PROTEINS. (June 2018) - Benaissa, Y.; Addou, S.; Kheroua, O.; Saidi, D.
Abstract : Objective: In the last few years a new preparation with coconut milk proteins was introduced and marketed as a useful alternative in the cases of cow's milk allergy. The objective of our work is to study the consequences of coconut milk on the structure of the intestinal epithelium. Design and method: For the histological study, 21 week-old mice Balb/c were used and distributed in three groups of 7 mice each. Group 1, received a standard feed with no treatment (Negative control), group 2 and 3 received respectively a standard feed (Positive control) and coconut milk for a period of 28 days after being immunized with alpha Lactalbumin. Results: Coconut milk also causes an increase of the intestinal villi height at the structure level of the intestinal mucous membrane of mice fed with coconut milk proteins compared to the positive control groups. The lymphocytic infiltration of mice fed with coconut milk proteins is similar to the one in negative control group. Conclusions: The preliminary results show that the coconut milk is a possible alternative to the cow's milk formula in case of allergy. Further studies are needed to prove its nutritional efficacy.